Pengaruh Gaya Hidup dan Citra Merek Terhadap Keputusan Pembelian Smartphone Xiaomi di Kabupaten Buleleng - Sriwahyuni, Novia; TeIagawathi, Ni Luh Wayan Sayang (Universitas Pendidikan Ganesha, 2021)
The objective of this research is to analyze the influence of lifestyle and brand image simultaneously and partially on purchasing decisions for Xiaomi smartphones in Buleleng Regency. The research framework used in this research is causal quantitative. The sample used in this research determined through accidental sampling. The number of samples used was 100 respondents. The research instrument used in data collection was a questionnaire and the data analysis technique done by using multiple linear regression analysis. The result of this research are: 1) lifestyle has a positive and significant effect on purchasing decisions for Xiaomi smartphones in Buleleng Regency, 2) Brand image has a positive and significant effect on purchasing decisions for Xiaomi smartphones in Buleleng Regency, and 3) Lifestyle and brand image have a significant effect on purchasing decisions for Xiaomi smartphones in Buleleng Regency.